Phenotypic variation in growth and biofilm formation of Leuconostoc spp. from sugar beet factories - Joshi, Sanjay; Bruni, Gillian O.; Zimmerman, Tia; Terrell, Evan; Salter, Johnathan; Kashem, Md Nayeem Hasan; Nam, Sunghyun (Frontiers in Microbiology, 2026)
Leuconostoc bacteria are common colonizers of sugar crop processing environments, resulting in sucrose losses and the formation of exopolysaccharides (EPS) and biofilms that can lead to reduced product quality and higher operational costs. Although Leuconostoc species are present in abundance, strain-specific differences in biofilm formation, EPS production, and matrix structure are not well understood. In this study, nine sugar beet factory-derived Leuconostoc isolates were grown and evaluated using a combination of batch adherence and continuous flow biofilm bioreactor assays, cryo scanning electron microscopy (SEM), EPS quantification, viscosity testing, and growth rate analysis to determine which phenotypes correlate with biofilm formation. The results from the adherence batch-phase biofilms indicated significant phenotypic variation among isolates, with the highest bacterial proliferation by L. suionicum BSDF25-7 and BSDF48-3, exceeding 5 × 108 colony-forming units/cm2 on stainless steel coupons. In contrast, the highest biofilm biomass accumulated was BSDF2-3 and BSDF25-7, indicating differences in cell proliferation and biofilm matrix structure. CryoSEM imaging revealed diverse biofilm structures, such as silo-like aggregates and patchy surface colonization, indicating strain-specific extracellular matrix assembly strategies. Flow-through biofilm bioreactor assays further identified BSDF2-3 and BSDF5-1 as predominant biofilm formers with the highest CFU/cm2 present at 4 × 108 and 1 × 109, respectively, while BSDF2-3 accumulated twice the biofilm biomass as BSDF5-1. Leuconostoc strains BSDF25-7 and BSDF48-3 produced high levels of dextran and EPS, while BSDF2-3 consistently formed dense, shear-resistant biofilms despite slow growth and low EPS levels, suggesting the possibility of alternative matrix composition or structural adaptations. Individual Leuconostoc strains adapt uniquely, adding to the functional diversity of biofilms that impact formation, matrix complexity, and resistance to environmental stressors. This study furthers our understanding of EPS and growth phenotypes involved in biofilm formation while providing a working model, enabling the development of future antimicrobial mitigation strategies.